Using A “Superrooting”Cultivar of Taxus Chinensis Var. Mairei to Unravel Antioxidative Enzymes’ and Micrornas’ Role on Adventitious Rooting - Wei Tang; Yongjun Fei (Journal of Enzymes, 2018)
Rooting of cuttings is very important for production of economically important plants. We produced thousands of plantlets in Taxus chinensisvar. mairei using the technology of rooting of cuttings and identified two types of rooted cuttings, one with low rate of root formation and another with high rate of root formation. To determine the physiological role of antioxidative enzymes and microRNAs during the process of rooting, we measured the levels of these antioxidative enzymes and microRNAs in the stem portion, needles, roots, and basal portion of cuttings. Compared to the cuttings with low rate of root formation, cuttings with high rate of root formation had higher expression of polyphenoloxidase (PPO), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APOX), glutathione reductase (GR), and superoxide dismutase (SOD) in the adventitious roots and basal portion of the rooted cuttings 77 days after planting. In the basal portion of cuttings, the content of thiobarbituric acid reactive substances (TBARS) and total phenols were decreased and the content of antioxidants was increased, but they did not changed in the needles of cuttings during planting. Analysis of microRNAs by quantitative realtime PCR demonstrated that expression of miR162, miR408, and miR857 increases in the basal portion of cuttings, but not in the stem portion of cuttings, 77 days after planting. Expression of miR408 and miR857 were also increased in the needles of cuttings 77 days after planting. Changes of these antioxidative enzymes and microRNAs associated with the rooting features of T. chinensisvar. maireicuttings and their functions have been discussed.
Keywords: Antioxidative enzymes